Respostas

2014-02-02T03:39:08-02:00
Olá Mascarado! 

Dado o problema, temos que:

\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}=\frac{11^{2\cdot3}\cdot13^{4\cdot3}}{11^{3\cdot2}\cdot13^{5\cdot2}}
\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}=\frac{11^{6}\cdot13^{12}}{11^{6}\cdot13^{10}}
\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}={11^{6-6}\cdot13^{12-10}}
\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}={11^{0}\cdot13^{2}}
\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}=1\cdot13^2
\frac{(11^2\cdot13^4)^3}{(11^3\cdot13^5)^2}=169

Abraço,

Douglas Joziel.
2014-02-02T18:33:47-02:00
 Resolva:
11elevado a 6 . 13elevado a 12    = 13 elevado a 12 =   13² = 169
11elevado a 6  . 13 elevado a 10      13 elevado a 10